Biphasic reward effects are characteristic of both lorcaserin and drugs of abuse: implications for treatment of substance use disorders. Issue 4 (23rd March 2022) - Grasing, Ken W.; Burnell, Kim; De, Alok
Abstract : Lorcaserin is a modestly selective agonist for 2C serotonin receptors (5-HT2C R). Despite early promising data, it recently failed to facilitate cocaine abstinence in patients and has been compared with dopamine antagonist medications (antipsychotics). Here, we review the effects of both classes on drug reinforcement. In addition to not being effective treatments for cocaine use disorder, both dopamine antagonists and lorcaserin can have biphasic effects on dopamine and reward behavior. Lower doses can cause enhanced drug taking with higher doses causing reductions. This biphasic pattern is shared with certain stimulants, opioids, and sedative-hypnotics, as well as compounds without abuse potential that include agonists for muscarinic and melatonin receptors. Additional factors associated with decreased drug taking include intermittent dosing for dopamine antagonists and use of progressive-ratio schedules for lorcaserin. Clinically relevant doses of lorcaserin were much lower than those that inhibited cocaine-reinforced behavior and can also augment this same behavior in different species. Diminished drug-reinforced behavior only occurred in animals after higher doses that are not suitable for use in patients. In conclusion, drugs of abuse and related compounds often act as biphasic modifiers of reward behavior, especially when evaluated over a broad range of doses. This property may reflect the underlying physiology of the reward system, allowing homeostatic influences on behavior.